2017
DOI: 10.1155/2017/1416375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Schinus terebinthifolius Raddi (Anacardiaceae) Bark Extract on Histamine‐Induced Paw Edema and Ileum Smooth Muscle Contraction

Abstract: Schinus terebinthifolius Raddi (Anacardiaceae), popularly known as red aroeira, is used in traditional medicine to treat inflammatory, gastric, and respiratory disorders. The aim of this study was to evaluate the antihistaminic activity of S. terebinthifolius (St) bark extract by using in vivo and in vitro experimental models. The effects of St were investigated on contractions induced by histamine, carbachol, and potassium chloride in isolated guinea pig ileum. St was also studied in response to hind paw edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…In traditional medicine, this plant is used to treat skin wounds and ulcers, tumors, diarrhea, arthritis as well as urinary and respiratory tract infections (Brandão et al, 2006). Various pharmacological activities have been described for this plant, including antimicrobial (Silva et al, 2017a), antiulcerogenic (Carlini et al, 2010), anticancer (Silva et al, 2017b), antihistamine (Nunes-Neto et al, 2017), antihypertensive (Glória et al, 2017), antihyperalgesic (Piccinelli et al, 2015), wound healing (Estevão et al, 2017), anti-inflammatory (Silva et al, 2017b) and antioxidant (Rocha et al, 2017) activities in different models.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, this plant is used to treat skin wounds and ulcers, tumors, diarrhea, arthritis as well as urinary and respiratory tract infections (Brandão et al, 2006). Various pharmacological activities have been described for this plant, including antimicrobial (Silva et al, 2017a), antiulcerogenic (Carlini et al, 2010), anticancer (Silva et al, 2017b), antihistamine (Nunes-Neto et al, 2017), antihypertensive (Glória et al, 2017), antihyperalgesic (Piccinelli et al, 2015), wound healing (Estevão et al, 2017), anti-inflammatory (Silva et al, 2017b) and antioxidant (Rocha et al, 2017) activities in different models.…”
Section: Introductionmentioning
confidence: 99%
“…7 ). These responses suggested that the extracts might induce competitive antagonism against the spasmogenic activity of histamine or 5-HT ( Nunes-Neto PA, et al 2017 ).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Schinus terebinthifolia Raddi, popularly known as "aroeira," is used in folk medicine for its antimicrobial, antiinflammatory, antiulcerogenic, febrifuge, analgesic, and depurative effects and to treat illnesses of the urogenital system and mucosal lesions (Cavalher-Machado et al, 2008;Lorenzi, Matos, 2008;Soares et al, 2007;Guerra et al, 2000). Antihistaminic (Nunes-Neto et al, 2017) and antihypertensive (Glória et al, 2017) activities have also been attributed to S. terebinthifolia in recent studies.…”
Section: Introductionmentioning
confidence: 90%